The Relationship between Healthcare Service Quality, Nurses’ Therapeutic Communication, and Inpatient Satisfaction at Labuang Baji Regional Hospital, Makassar - Andi Sahrul; Fatmah Afrianty Gobel; Haeruddin Haeruddin (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the relationship between the quality of health care—based on the dimensions of Public Hospital Service Quality (PubHosQual)—and nurses’ therapeutic communication on the satisfaction of inpatients at Labuang Baji Regional General Hospital in Makassar. Research Method: This study employed a quantitative approach with a cross-sectional design. The sample consisted of 154 inpatients selected using purposive sampling from a population of 252 patients. Data were collected via a structured questionnaire and analyzed using the Chi-Square test and multiple logistic regression. Results and Discussion: The results of the study show that all dimensions of healthcare quality (patient admission, medical services, overall services, hospital discharge, and hospital social responsibility) as well as all stages of therapeutic communication (pre-interaction, orientation, working stage, and termination) are significantly associated with patient satisfaction (p < 0.05). Multivariate analysis showed that the services provided by doctors and nurses (OR = 50.500; p = 0.013) and the termination stage of therapeutic communication (OR = 101.000; p = 0.008) were the most dominant factors associated with patient satisfaction. Implications: These findings serve as a basis for hospitals to improve the quality of medical care and the use of therapeutic communication—particularly during the end-of-care phase—in order to enhance patient satisfaction Originality: This study integrates the five dimensions of PubHosQual and the four stages of therapeutic communication into a single analytical model to explain inpatient satisfaction at government hospitals.